2010
DOI: 10.1155/2010/236405
|View full text |Cite
|
Sign up to set email alerts
|

CD14CD16 Monocyte Subset Levels in Heart Failure Patients

Abstract: Abstract.Our aim was to define the distribution of monocyte subsets in a cohort of congestive heart failure (CHF) patients, to verify whether increased severity of CHF is linked to the expansion of specific monocyte subsets, and finally to investigate the relationship between monocyte subset relative frequencies, laboratory parameters of inflammation, and monocyte ACE expression. Thirty consecutive CHF patients and 26 healthy control subjects were evaluated for peripheral blood monocyte expression of CD14, CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 27 publications
(32 reference statements)
6
55
0
3
Order By: Relevance
“…It suggests that aberrant immune activation is present in T2DM patients and uremic DN patients, in agreement with the results of Du et al [20]. Given the fact that CD14 + CD16 + monocytes represent a sensitive marker for inflammation or cellular activation, the role of CD14 + CD16 + monocytes in various diseases have received considerable interest in recent years [24][25][26][27]. And there is a host of reports [22,[24][25][26][27] about increases or decreases in the number of CD14 + CD16 + monocytes in various diseases.…”
Section: Discussionsupporting
confidence: 84%
“…It suggests that aberrant immune activation is present in T2DM patients and uremic DN patients, in agreement with the results of Du et al [20]. Given the fact that CD14 + CD16 + monocytes represent a sensitive marker for inflammation or cellular activation, the role of CD14 + CD16 + monocytes in various diseases have received considerable interest in recent years [24][25][26][27]. And there is a host of reports [22,[24][25][26][27] about increases or decreases in the number of CD14 + CD16 + monocytes in various diseases.…”
Section: Discussionsupporting
confidence: 84%
“…Within AAA patients, decreased counts of CD14 dim CD16 + monocytes were observed in patients with the highest circulating counts of neutrophils and of total white blood cell counts. We previously made this observation in a cohort of CHF patients with a reduced ejection fraction of the left ventricle [17]. We then attributed this finding to a distinct pattern of transendothelial migration between CD16…”
Section: Discussionmentioning
confidence: 77%
“…Angiotensin converting enzyme (ACE), detected as CD143, is present at high levels on monocytes [15]. Monocytic ACE expression was found highest among CD14 + CD16 + monocytes; monocyte CD143 expression was increased in dialysis patients with prevalent cardiovascular disease and in patients with congestive heart failure (CHF) [16,17]. Alterations in monocyte CD143 expression might be related to the process of vascular damage during development of atherosclerotic and of AAA lesions [18,19], since the product of CD143, angiotensin II, promotes pro-oxidant bursts, endothelial release of proinflammatory cytokines and leukocyte adhesion to the vessel wall [20].…”
Section: Introductionmentioning
confidence: 99%
“…10 The specific role of monocytes in HF is largely unknown, although monocyte levels are increased in patients who develop LV dysfunction after myocardial infarction (MI), and a recent study also demonstrated increased monocyte numbers in patients with stable systolic HF. 11 Furthermore, monocytes are heterogeneous and consist of distinct subpopulations with differing phenotype and functional characteristics. 12,13 These subsets can be defined by flow cytometry according to differential expression of surface markers, giving rise to classic CD14++CD16-CCR2+ (Mon1), intermediate CD14++CD16+CCR2+ (Mon2), and nonclassic CD14+CD16++CCR2-(Mon3) subsets.…”
mentioning
confidence: 99%